Utilization of Drivers’ Dynamic Visual Characteristics to Find the Appropriate Information Quantity of Traffic Engineering Facilities on Straight Roads of Grassland Highways - Li, Hangtian; Xie, Songfang; Yang, Feng; Lu, Yang; Zhu, Shoulin (Frontiers in Neuroscience, 2022)
In order to find the appropriate range of information quantity, this paper studied how the information quantity of traffic engineering facilities (TEF) on straight roads of grassland highways affects a driver's eye movements. This paper used a combination of survey, statistics, analysis of variance and the establishment of virtual scene to do the research, and carried out simulated driving tests at six levels (Z0, Z1, Z2, Z3, Z4, Z5) of TEF information quantity. The driver's fixation duration, visual search breadth and glance speed were evaluated in a quantitative way. Results showed that the information quantity had significant impact on eye movements. It is concluded that the information quantity from 0 to 10 bits/km may cause problems to drivers, whereas the information quantity of 40 bits/km serves as the limit. The information quantity from 30 to 40 bits/km is the appropriate one for TEF on grassland highways.